SPIDER DIVERSITY (ARACHNIDA: ARANEAE) OF THE TEA PLANTATION AT SERANG VILLAGE, KARANGREJA SUB-DISTRICT, DISTRICT OF PURBALINGGA - Gianti Sibarani; Imam Widhiono; Darsono Darsono (Scripta Biologica, 2017)
Spiders are crucial in controlling insect pest population. The various cultivation managements such as fertilizer and pesticide application, weeding, pruning, harvesting, and cropping system affect their diversity. In the plantation, vegetation diversification has applied various practices, including monoculture, and intercropping, which influence the spider community. Thus, this study was intended to determine the spider abundance and diversity of the tea plantation, and the intercropping field (tea and strawberry) at Serang village, Karangreja Sub-District, District of Purbalingga. A survey and purposive sampling techniques were conducted, then the spiders were hand collected. Shannon-Wiener diversity (H’), Evenness (E), Simpson’s dominance (D), and Sorensen’s similarity (IS) indices were used to measure the spider diversity. The results revealed a total number of 575 individual spiders from 10 families, i.e., Araneae, Araneidae, Clubionidae, Linyphiidae, Lycosidae, Nephilidae, Oxyopidae, Salticidae, Tetragnathidae, Theridiidae, and Thomisidae. Araneidae was the most abundant in both fields. The total abundance of spiders in tea plantation (379 individuals), however, was greater than that in the intercropping field (196 individuals). Shannon-Wiener diversity reached H’= 1.873 in the plantation, and H’= 1.975 in the intercropping field.